Developing an Interactive Web System for Public Service at BPS Boyolali - Adi Nugrah Sri Pangestu; Moh.Muhtarom; Nibras Faiq Muhammad (bit-Tech, 2025)
This study presents the development of a web-based system aimed at enhancing public services at the Mall Pelayanan Publik (MPP) of the Badan Pusat Statistik (BPS) in Boyolali. Built on the Next.js framework, the new system addresses key inefficiencies in previous manual and semi-digital approaches, such as those based on Google Forms. It introduces a streamlined integration of Google Sheets for data management and the BPS API for real-time statistical updates, providing an automated, efficient process for visitor data recording and service delivery. The system’s core features include automatic logging of visitor data, a Q&A platform with BPS staff, real-time notifications for administrators, and personalized data recommendations tailored to user interactions. Developed using a prototyping methodology, the system underwent iterative refinement based on user feedback, while a PIECES framework analysis was employed to evaluate and guide the system’s improvements. Implementation results indicate significant enhancements in data management, admin response times, and overall user interface interactivity, thereby improving service efficiency, transparency, and public engagement at BPS. Despite its successes, the system faces limitations, including its reliance on stable internet connectivity and potential scalability issues with Google Sheets. Future upgrades may focus on advanced data analytics and optimization of the user interface. This research contributes to the growing field of digital transformation in public service delivery, presenting a scalable model that could be applied to similar public institutions.